Вплив суперпозиції на квантові властивості випромі-нювання з порожнини трирівневого лазера - Ayehu, D.; Chane, A. (Publishing house "Academperiodika", 2021)
We study the statistical and squeezing properties of the cavity light produced by a degenerate three-level laser with the use of the solution of the pertinent quantum Langevin equation. Moreover, applying the density operator to the cavity radiation superposition, we investigated the quantum properties of the superposed cavity light beams generated by a pair of degenerate three-level lasers. Superposing the cavity radiation increases the mean and the variance of the photon number without affecting the quadrature squeezing. It is observed that the degree of squeezing of the separate cavity radiation, as well as the superposed cavity radiation, increases with the rate at which the atoms are injected into the cavity. We have also shown that the mean photon number of the superposed cavity radiation is the sum of the mean photon numbers of the individual cavity radiation. However, the variance of the photon number of the superposed cavity radiation turns out to be four times that of the component cavity radiation.